1994
DOI: 10.1016/1044-0305(94)85061-5
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition in the gas phase: Mass spectrometric studies of diastereomeric cobalt complexes

Abstract: Results of mass analyzed ion kinetic energy (MIKE) spectra and kinetic energy release (KER) measurements of diastereomeric octahedral cobalt complexes indicate that these diastereomers can be distinguished in the gas phase. Four alkyl tartrate esters were complexed to cobalt trisacetylacetonate (Co(acac)3) in the presence of a chiral auxiliary, RR- and SS-threohydrobenzoin. Different KER values of the product ion generated from [Co(acac)2/D- or L-diisopropyl tartrate](+) reflect differences in the precursor io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
1
27
1
Order By: Relevance
“…The chiral recognition ratios R as given in Equation 2 vary between 0.3 and 3 for 19 different amino acids under study (Yao et al, 1999). The tartrates have also been studied as transition metal complexes (Dang et al, 1994;Arakawa et al, 2000). Thus, it seems obvious to examine the chirality effects in transition metal complexes of amino acids.…”
Section: Molecular Recognition and Supramolecular Chemistrymentioning
confidence: 98%
“…The chiral recognition ratios R as given in Equation 2 vary between 0.3 and 3 for 19 different amino acids under study (Yao et al, 1999). The tartrates have also been studied as transition metal complexes (Dang et al, 1994;Arakawa et al, 2000). Thus, it seems obvious to examine the chirality effects in transition metal complexes of amino acids.…”
Section: Molecular Recognition and Supramolecular Chemistrymentioning
confidence: 98%
“…The gas-phase mass spectrometric methods that have been extensively developed fall into five main categories: (1) the kinetic method formalism , (2) host-guest (H-G) diastereomeric adduct formation [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], (3) ion/molecule (equilibrium) reactions [68][69][70][71][72][73][74][75], (4) CID of diastereomeric adducts [76][77][78], and (5) the emerging technique of ion mobility spectrometry (IMS) [131][132][133][134][135][136]. These methods along with other mass spectrometric approaches [79][80][81][82][83][84][85][86][87][88][89] provide a fast means for gas-phase chiral analysis.…”
Section: Advances In Gas-phase Mass Spectrometric Methods For Chiral mentioning
confidence: 99%
“…+ (acac = acetylacetonate ion) and it was concluded that the presence of a chemical kinetic resolving agent like RR-or SS-threohydrobenzoyn (THB) is essential for this chiral recognition system [71]. The enantiomers of analytes, such as isopropyl threo-and erythro-3-cyclohexylglycerates, 2,3-butanediol, trans-1,2-cyclohexanediol, and 1,4-dimethoxy-2,3-butanediol were studied in the gas phase by CI-MS using labeled diisopropyl tartrates as a chiral reference [75].…”
Section: Gas Phase Molecular Recognition Properties Of Tartratesmentioning
confidence: 99%